Dietary choline supplementation in adult rats improves performance on a test of recognition memory - Moreno, Hayarelis; Hall, Geoffrey; Gallo, Milagros; de Brugada, Isabel (Behavioural brain research, 2018)
In two experiments adult rats (aged at least 6 months at the start of the procedure) received a diet enriched with added choline for a period of 10 weeks; control subjects were maintained on a standard diet during this time. All rats then underwent the spontaneous object recognition (SOR) procedure in which they were exposed to a pair of objects and then tested, after a retention interval, to a display with one object changed. Exploration of the changed object indicates retention and use of information acquired during the exposure phase. All subjects showed retention with a 24-h interval (Experiments 1 and 2) and when retested after a further 24 h (Experiment 1). But when tested for the first time after a 48-h interval (Experiment 2), control subjects showed no evidence of retention, exploring both objects equally, whereas those given the dietary supplement continued to show a preference for the changed object. This supports the conclusion that dietary choline supplementation can enhance performance on a task regarded as a test of declarative memory, and will do so even when the supplementations is given in adulthood.